Effectiveness of Chayote Extract on Lowering Blood Pressure of Post Partum Hypertension - Dwi Apriyani; Masrifan Djamil; Suryati Kumorowulan (Universitas STRADA Indonesia, 2020)
Post partum hypertension contributes to maternal mortality. Postpartum hypertension management can be in the form of pharmacological therapy, but it causes side effects for mother and baby. Several studies have shown that chayote can play a role in lowering blood pressure. This research aimed to prove the effect of chayote extract on reducing blood pressure in postpartum with hypertension. Quasy experiment pretest and posttest control group design. The number of samples was 19 interventions and 19 controls. The intervention group received 400 mg of chayote extract and 10 mg of nifedipine, while the control group received only 10 mg of nifedipine. The intervention was carried out for 7 days. The treatment group experienced significant changes in systolic blood pressure and diastolic blood pressure with p value = 0.000 compared to the control group. The chayote extract has a significant effect on reducing blood pressure in postpartum with hypertension